Crop growth analysis of wheat cultivars under different hydrothermal regimes - Kaur, Navneet; Gill, K. K. (Annals of Agricultural Research, 2016)
The growth analysis based on crop growth rate and net assimilation rate was done for the wheat crop. The field experiment was conducted at Research farm, School of Climate Change and Agricultural Meteorology, Punjab Agricultural University, Ludhiana during the winter season 201112 and 2012-13. The experiment was laid out in Split-split plot design with three sowing dates in main plots (November 15, November 25 and December 5), four irrigation levels in sub-plots I1 (irrigation at CRI, jointing and milking), I2 (irrigation at CRI, tillering, booting and milking), I3 (irrigation at CRI, tillering, jointing, booting and milking) and I4 (irrigation according to weather forecast) and two wheat varieties in sub-sub plots (PBW 343 and PBW 621). The results showed that November 15 sown crop had higher value of growth rate parameters followed by November 25 and December 5 sown crops. Similarly, among irrigation treatments, the unstressed irrigation treatments with irrigation at I3 and I4 level showed higher growth rate as compared to others in cultivar PBW 621. It was also found that growth parameters gave highest values during 2011-12 contributed towards more yield and yield contributing characters as compared to 2012-13.